Robust adaptive tracking control for air-breathing hypersonic vehicles - Zhiling Yang; Bin Meng; Hongfei Sun (Chinese Control and Decision Conference, 2014)
This paper focuses on the adaptive tracking problem for air-breathing hypersonic vehicles (AHVs) subject to aerodynamic uncertainties and unknown disturbances caused by modeling errors. Motivated by the nonlinear disturbance observer-based control approach (NDOBC), the parameter uncertainties are merged into the disturbances. A control law based on the tracking control method originally proposed by Sun et al. (2013) is designed to achieve the desired tracking objective. The adaptation law used to update the disturbances estimates can be synthesized by usual adaptive control techniques. Different from the backstepping method, this control method does not need to transform the system model into a strict-feedback form. Simulation results show its effectiveness.